SETD8 involved in the progression of inflammatory bowel disease via epigenetically regulating p62 expression. Issue 10 (29th May 2021) - Chen, Ping; Zhu, Hua; Mao, Yujuan; Zhuo, Mingxing; Yu, Yali; Chen, Min; Zhao, Qiu; Li, Lianyun; Wu, Min; Ye, Mei
Abstract: Background and Aim: Epigenetic modification is an important part of the pathogenesis of inflammatory bowel disease (IBD). Some studies proved that p62 was involved in inflammatory response and upregulated in IBD patients, and histone modification plays an important role in regulating p62 expression. SETD8, a histone H4K20 methyltransferase, has been reported downregulated in some inflammatory diseases. Here, we investigated the role of SETD8 in the development of IBD and its underlying mechanisms. Methods: An inflammatory cell model was established to elucidate whether SETD8 involved in inflammatory response in macrophages. Three percent dextran sodium sulfate‐induced colitis murine model injection with SETD8 inhibitor was used in our study to investigate whether SETD8 inhibition can affect the progress of IBD. The expression of SETD8 and p62 was measured by qRT‐PCR and western blot. The mRNA level of inflammatory cytokines was analyzed by qRT‐PCR. In addition, chromatin immunoprecipitation‐PCR was performed to identify the mechanism by which SETD8 regulates p62. Results: SETD8 expression obviously decreased in vitro, in vivo models and in IBD patients. In lipopolysaccharide‐activated RAW264.7 cells, knockdown of SETD8 significantly increased the mRNA expression of inducible nitric oxide synthase, cyclooxygenase‐2, TNF‐α, IL‐6, IL‐1β, and MCP‐1 . Based on the dataset, we verified that p62 was a target gene of SETD8 and chromatin immunoprecipitation‐PCR assay identified that silence of SETD8 distinctly decreases the H4K20me1 enrichment in the promoter of p62. Moreover, silencing of p62 partly reverses the SETD8 inhibition‐mediated pro‐inflammatory effect in vitro . Finally, SETD8 pharmacological inhibitor (UNC0379) aggravated the disease progression in dextran sodium sulfate‐induced murine colitis. Conclusion: Our findings elucidate an epigenetic mechanism by which SETD8 regulates the p62 expression and restrains the inflammatory response in colitis. Our result suggests that targeting SETD8 may be a promising therapy for IBD.